2016
DOI: 10.1093/gerona/glw036
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Impairments and Risk of Mortality in Older Adults

Abstract: Olfactory impairment, but not hearing or visual impairment, was associated with an increased risk of mortality. These results suggest that olfactory impairment may be a marker of underlying physiologic processes or pathology that is associated with aging and reduced survival in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
132
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(149 citation statements)
references
References 44 publications
13
132
0
4
Order By: Relevance
“…Clinicians are increasing focus toward olfactory impairment, a cardinal symptom used to diagnose CRS, due to its direct and indirect effects on behavior, nutritional status, and environmental safety . A recent study even linked smell loss to increased mortality, a finding not seen with hearing or vision loss . Understanding the scope of CRS‐related olfactory dysfunction benefits multiple stakeholders, including patients, physicians, researchers, and healthcare policy makers.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians are increasing focus toward olfactory impairment, a cardinal symptom used to diagnose CRS, due to its direct and indirect effects on behavior, nutritional status, and environmental safety . A recent study even linked smell loss to increased mortality, a finding not seen with hearing or vision loss . Understanding the scope of CRS‐related olfactory dysfunction benefits multiple stakeholders, including patients, physicians, researchers, and healthcare policy makers.…”
Section: Introductionmentioning
confidence: 99%
“…Multisensory loss appears to be common in older U.S. adults but has been little studied. There are specific neurophysiological changes associated with aging that could increase dysfunction in all senses .…”
mentioning
confidence: 99%
“…One study showed no excess of mortality among prelingually deaf people compared with hearing controls, although a small excess in mortality was observed for postlingually deafened individuals (Barnett and Franks 1999), again possibly reflecting adjustment and coping difficulties. In the USA, Schubert et al (2017) studied the associations between hearing, visual, and olfactory impairments with mortality and somewhat surprisingly found that olfactory impairment, but not hearing or visual impairment, was associated with an increased risk of mortality. In Iceland, older men with hearing impairment or dual sensory impairment (vision + hearing loss) had a greater risk of dying from any cause and particularly cardiovascular causes within a median 5-year follow-up.…”
Section: Implications Of Early Hearing Loss For Health Development Ovmentioning
confidence: 99%